Citizens Speaking as Experts: Expertise Discourse in Deliberative Forums. Issue 3 (3rd April 2018) - Sprain, Leah; Reinig, Lydia
ABSTRACT: By analysing how participants use expertise discourse during environmental forums, this study examines how expert and lay knowledge are infused in deliberative democracy and the necessary distinctions between ways of knowing within deliberative epistemology. Through Grounded Practical Theory and Communication as Design, we analyse how expertise discourse contributes to and might undermine democratic deliberation through empirical analysis of transcripts from environmental forums in the United States. Our analysis describes three forms of expertise discourse used by participants within deliberative forums: institutional expertise, local expertise, and issue expertise. Expertise discourse is co-produced between participants, contributes to the information base, and most frequently comes in the form of institutional expertise. This discourse practice poses two problems for deliberative democracy: participants presenting information as an evident solution, and expertise discourse creating hierarchies that foreclose participation. We offer design recommendations for how to manage these problems within environmental forums.